miRNAs 144-3p, 34a-5p, and 206 are a useful signature for distinguishing uterine leiomyosarcoma from other smooth muscle tumors - Beatriz Nunes Schiavon; Katia Candido Carvalho; Cláudia Malheiros Coutinho-Camillo; Glauco Baiocchi; Renan Valieris; Rodrigo Drummond; Israel Tojal da Silva; Louise De Brot; Fernando Augusto Soares; Isabela Werneck da Cunha (BMC, 2019)
Abstract Background Leiomyosarcoma (LMS) is a rare uterine neoplasm that has a high mortality rate and no specific treatment. The origin of LMS remains unknown; although, it is hypothesized that LMS arises from the malignant transformation of a degenerated uterine leiomyoma (LM). LMs are the most common benign tumors diagnosed and rare variants of LM (unconventional LM) morphologically resemble LMS, thereby making an early and precise diagnosis of LMS difficult. Various molecular features may influence the malignancy risk of LMS tumors, including microRNAs (miRNAs). However, the role of miRNAs in uterine mesenchymal tumors remains poorly understood. Here, our aim was to assess the miRNA expression profiles of LMS, LM, and LM variants (ULM) to identify a specific signature that may facilitate differentiation among these tumor types. Possible associations between these profiles and patients' clinical and pathological features were also analyzed. Methods Total RNA was extracted from formalin-fixed paraffin-embedded tissue samples of uterine LMS (n = 37), LM (n = 3), ULM (n = 8), and myometrium (MM) (n = 2) to perform real-time PCR analyses and detect expression levels of a panel of 84 miRNA sequences related to cancer. Results Between the LMS and LM samples, 16 miRNAs were found to be differentially expressed, with miR-372 and miR-34a-5p exhibiting the highest and lowest levels of expression, respectively. When LMS and ULM were compared, 5 differentially expressed miRNAs were identified, with miR-34a-5p downregulated and miR-144-3p upregulated. Between ULM and LM, all of the differentially expressed miRNAs were upregulated, and miR122-5p exhibited 10-fold higher expression. In addition, significant correlations were found between various miRNAs and tumor relapse (miR-148a-3p), metastasis (miR-27b-3p), and patient death (miR-124-3p and miR-183-5p). Downregulation of miR135b-5p was associated with disease-free survival. Conclusion Expression profiling of miRNAs 144-3p, 34a-5p, and 206 may be useful in characterizing uterine LMS and distinguishing it from benign tumors. Furthermore, deregulation of miRNAs 148a-3p, 27b-3p, 124-3p, 183-5p, and 135b-5p appear to indicate a poor prognosis for LMS patients.